Commercial Cloud Services for a Robust Mobile Application Backend Data Storage - Dahunsi, Folasade M; Idogun, John; Olawumi, Abayomi (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2021)
Rapid advancements in the infrastructure of Information and Communication Technology (ICT) have led to radically new but ubiquitous technology; cloud computing. Cloud computing has gracefully emerged offering services that possess on-demand scalability, huge computing power, and a utility-like availability, all at a relatively low cost. It has unsurprisingly become a paradigm shift in ICT, gaining adoptions in all forms of application i.e., personal, academic, business, or government. Not only for its cost-effectiveness but also for its inherent ability to meet business goals and provide strategic ICT resources. More recently there have been advances in cloud computing leading to the evolution of newer commercial cloud services, one of which is the Mobile backend as a Service (MBaaS). The MBaaS is important and required for a robust mobile application back-end data storage and management. Its wide adoption and importance stem from its ability to simplify application development and deployment. Also, MBaaS is robust, with the ability to cope with errors by providing nifty tools and other features. These enable rapid scaffolding of mobile applications. This paper reviews Mobile backend as a Service (MBaaS) and provides required background knowledge on some cloud services and their providers to enable stakeholders to make informed decisions and appropriate choices.